Analysis of electromechanical characteristics of the 1-3-2 piezoelectric composite and 1-3-2 modified structural material. Issue 15 (1st August 2022) - Wang, Hongwei; Li, Yang; Hui, Hui; Rong, Tian
Abstract: In this study, a piezoelectric material with a modified structure was designed and fabricated based on a 1-3-2 piezoelectric composite, in an attempt to improve the thickness vibration electromechanical coupling coefficient of the piezoelectric sensitive element of transducer. No polymer was injected into the ceramic column arrays, and the upper surface of the ceramic column was covered with a metal plate, thereby reducing the lateral coupling among the piezoelectric columns. Thus, reducing the loss, and effectively improving the thickness vibration electromechanical coupling coefficient. The thickness vibration modes and electromechanical coupling coefficient of the 1-3-2 piezoelectric composite and 1-3-2 modified structural material were studied by theoretical analysis, simulation, and experiment. The results show that for the thickness vibration, the electromechanical coupling coefficient of the modified structural material increases by about 6% compared with the 1-3-2 piezoelectric ceramic/epoxy composite.